EXISTING PROBLEMS IN LOGISTICS SYSTEMS AND THEIR ANALYSIS - KUCHAROVA SHAXLO SOBIR QIZI (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This study examines existing problems in logistics systems and analyses the level of digital technology usage in logistics operations, particularly in small enterprises. The research highlights that digital technologies play an important role in transportation management, warehouse operations, inventory control, order processing, and delivery planning and monitoring. The study shows that the use of digital technologies such as automated management systems, big data analytics, artificial intelligence, the Internet of Things, and cloud computing significantly improves logistics efficiency, reduces operational costs, and increases supply chain stability. The paper also identifies major logistics problems in small enterprises, including high transportation costs, insufficient warehouse equipment, lack of qualified logistics specialists, limited IT systems, and inefficient inventory management. The results indicate that the integration of digital technologies into logistics systems improves operational efficiency, decision-making quality, and overall competitiveness of enterprises. The study concludes that increasing the level of digitalisation in logistics systems is an important factor for improving logistics performance and ensuring sustainable economic development.